Validation of Seismic Performance of Stainless Press-to-Connect Piping System under Cyclic Loadings - Bu-Seog Ju; Bub-Gyu Jeon; Sung-Wan Kim; Ho-Young Son (Applied Sciences, 2022)
Earthquakes with magnitudes over 5.0 occurred near Gyeongju and Pohang in southern Korea in 2016 and 2017, respectively. These earthquakes had both low- and high-frequency components. Due to earthquakes with high-frequency motions, damage to nonstructural systems has been observed to be relatively more than that in structural systems. Consequently, the seismic design or performance evaluation of nonstructural components in critical facilities has emerged as a key research area in Korea. This study presents the results of experimental and numerical analyses using a high-fidelity finite element (FE) simulation in the ABAQUS platform for a press-to-connect piping system as a nonstructural component. Press-to-connect piping systems based on NFPA-13 with two elbows, a flexible coupling, and a T-joint were used. In addition, a cyclic loading protocol was applied using the KBC 2016 and IBC 2015. Based on the component-level experimental test, an FE model of the press-to-connect elbow was developed, and the high-fidelity large-scale piping system with an elbow was validated in this study. In both the experimental and analytical results, no leakage or plastic deformation of the piping system was observed under cyclic loading conditions. The results of the high-fidelity simulation model of the large-scale piping system were identical to those of the experimental test. More specifically, the error of the von-Mises stress at the upper and lower elbows was less than 9%, and the angle between the elbows was less than 2%, corresponding to the limit state of the drift ratio of the building system. Therefore, the high-fidelity simulation model of a large-scale piping system can have high application value. In addition, the design requirements and engineering demands of the piping system, such as the condition of ASME B and PV section III for service level D, were satisfied.